Biased Survival Beliefs, Psychological and Cognitive Explanations, and the Demand for Life Insurances - Nils Grevenbrock; Max Groneck; Alexander Ludwig; Alexander Zimper (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper presents new findings on biased survival beliefs by constructing their individual-level objective counterparts. We find that biases can be modelled through age-dependent probability weighting functions as known in cumulative prospect theory. The dynamics of these probability weighting functions over age suggest that misconception is increasingly driven by pessimism and likelihood insensitivity. These findings are in line with rationalizations in the literature using structural behavioral learning models with psychological biases. Exploiting newly available data from the Health and Retirement Study (HRS) on psychological factors we provide further empirical evidence supporting these explanations. Finally, we show that misconception is relevant for the demand for life insurance.
Keywords: D12; D83; I10; 330